ANALISIS STRATEGI PENGEMBANGAN KEBUN AGROMEDIKA HAMBARO (Ã¢â‚¬ÂKAMAROÃ¢â‚¬Â) SEBAGAI KEBUN WISATA EDUKATIF BUDIDAYA TANAMAN OBAT - gunarto, anton (Jurnal Sains dan Teknologi Indonesia, 2011)
Kebun Agromedika Hamboro (Kamaro) is cultivation of medicinal plants demonstration farm (demfarm), especially rhizome plants. The purpose of this research is to identify the internal conditions (strengths and weaknesses) and external (opportunities and threats) Kamaro and to provide alternative strategies that can be applied in the development of educational tourism Kamaro as a garden of medicinal plants. Theresults showed that the IFE matrix that became a major force Kamaro factors include the product being offered is a useful medicinal plants for health, while its main weakness is a condition of the garden is not good. The results showed that EFE matrix is a major opportunity Kamaro factor is the development of science and technology so as to incrase business transactions, while the threat factor is climate and weather nature conditions are unpredictable. Based on the IE matrix results, Kamaro puts on depicting V cells in the internal conditions of the average and Kamaro response to external factors faced by relatively moderate. The strategy can be implemented is to preserve and maintain, an alternative strategy that many do is market penetration and product development. Results of the SWOT matrix are obtained seven alternative strategies. The results matrix QSP is obtained main strategic priority to improve the management system such as increase farm productivity, post-harvest handling, gardensanitation and magnificence, administration and finance and others.